Best Paper Award 2013 - Kyriakidis, Phaedon (My University, 2026)
Mathematical Geosciences publishes 48 high-quality papers each year. Among all of those, we have set ourselves the arduous task of selecting the most exceptional one. Now a well-known yearly tradition, the Editorial Board and Editorial team are pleased to announce the winner of the 2013 Best Paper Award: “Efficient Simulation of (Log)Normal Random Fields for Hydrogeological Applications” by Phaedon Kyriakidis and Petros Gaganis, Mathematical Geosciences, 45 (6):531–556.
Keywords: Sciences